Technical progress as a factor of economic growth in the classical theory of J. S. Mill - Pasichnyk, Taras (Herald of Economics, 2025)
Introduction. J. S. Mill is traditionally regarded as a thinker who summarized the achievements of classical political economy, but his approach is much broader, as he integrates economics into the context of social philosophy. J. S. Mill sought to provide a comprehensive interpretation of socio-economic issues, including the distribution of roles between the state and the market, the organization of production, and the impact of technology on labor. His vision of economic growth includes not only capital accumulation, but also the role of institutions, ethics, and technological progress. Of particular importance is the idea of the “antagonistic principle,” which reveals the compensatory function of innovation in relation to natural and social constraints. Despite the relevance of these ideas in the context of modern challenges, J. S. Mill’s contribution to growth theory is still underestimated.Objective. The modern interpretation of J. S. Mill’s theory of economic growth, considering the importance of innovative factors within the classical paradigm of political economy.Methods. To achieve this goal, hermeneutical analysis (to identify the content, hidden meanings and logical structure of J. S. Mill’s growth concept), historical, genetic and comparative analytical methods, as well as conceptual and mathematical modeling are used.Results. J. S. Mill’s theory of economic growth is reconstructed as an open dynamic system that combines technological progress, institutional factors and social philosophy. The key role of the “antagonistic principle” as a mechanism that allows technical innovations to compensate for natural and social constraints on production is highlighted. A mathematical interpretation of J. S. Mill’s approach based on I. Adelman’s generalized growth model with regard to institutional and innovative variables is proposed. It is shown that the concept of steady state in his theory does not imply stagnation, but a transition to a qualitatively new type of development.Prospects for further research lie in the mathematical extension of J. S. Mill’s growth model by constructing a production function with endogenous technological and institutional variables. In addition, a comparative analysis, in particular, a comparison of J. S. Mill’s ideas with modern concepts of sustainable development and the “happiness economy”, is a promising direction.